One approach to artificial photosynthesis - Llansola Portolés, Manuel Jose (2013)
Research in artificial photosynthesis includes experiments designed to elucidate the fundamental principles governing natural photosynthesis and their application to the design of synthetic solar energy conversion systems. Artificial systems are not intended to exactly reproduce the natural process, but rather to adapt its basic principles in order to achieve the production of fuel or electricity with improved efficiency. As in natural photosynthesis, an artificial reaction center for solar fuel production should absorb light in the visible and near-infrared regions of the solar spectrum, generate a charge-separated state, spatially separate and stabilize the charges and transport the photo-generated oxidizing and reducing equivalents to catalysts which carry out the chemical reactions necessary for the production of a fuel (e.g., production of H2 by electrons obtained from the oxidation of water). Much of the research of the Gust, Moore, and Moore (GMM) group has been centered on the development and study of artificial reaction centers with the dual objectives of reaching a better understanding of photosynthesis and developing bio-inspired solar-to-fuel systems. In the work outlined below, several examples from the GMM group are used to illustrate the research trajectory aimed at this ultimate goal.